2016
DOI: 10.1016/j.adolescence.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

What parents don't know: Disclosure and secrecy in a sample of urban adolescents

Abstract: Research with two-parent European households has suggested that secrecy, and not disclosure of information per se, predicts adolescent adjustment difficulties. The present study attempted to replicate this finding using data from a 4-wave study of 358 poor, urban adolescents (47% male; M age = 12 yrs) in the United States, most of whom (> 92%) were African American. Adolescents self-reported secrecy, disclosure, depressive symptoms, and delinquency at each wave. Confirmatory factor analyses revealed that a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
(127 reference statements)
1
19
0
4
Order By: Relevance
“…Then again, earlier studies with Western adolescents predominantly measured adolescent disclosure as a mixture of disclosure and secrecy (Stattin and Kerr 2000) (rather than separating these two constructs as proposed by Frijns et al 2010) and often investigated externalizing (e.g., Racz and McMahon 2011) rather than internalizing problems. One exception is a study by Hamza and Willoughby (2011) where a negative link from adolescent depressive symptoms to disclosure was found among Canadian mid-adolescents and a study by Jäggi et al (2016) where a negative link between depressive symptoms to secrecy was found among US Black preadolescents. Thus, specific prospective links between adolescent disclosure, secrecy, and internalizing among early adolescents have rarely been studied prior to the present investigation, and less is known about these links worldwide.…”
Section: Are the Links Between Parent-adolescent Communication Effortmentioning
confidence: 99%
“…Then again, earlier studies with Western adolescents predominantly measured adolescent disclosure as a mixture of disclosure and secrecy (Stattin and Kerr 2000) (rather than separating these two constructs as proposed by Frijns et al 2010) and often investigated externalizing (e.g., Racz and McMahon 2011) rather than internalizing problems. One exception is a study by Hamza and Willoughby (2011) where a negative link from adolescent depressive symptoms to disclosure was found among Canadian mid-adolescents and a study by Jäggi et al (2016) where a negative link between depressive symptoms to secrecy was found among US Black preadolescents. Thus, specific prospective links between adolescent disclosure, secrecy, and internalizing among early adolescents have rarely been studied prior to the present investigation, and less is known about these links worldwide.…”
Section: Are the Links Between Parent-adolescent Communication Effortmentioning
confidence: 99%
“…First, previous research suggests that many of the variables that were included in the model are reciprocally related (Tilton-Weaver 2014). For example, adolescent substance use and delinquency contributes to concealing information from parents (Jaggi et al 2016), but a tendency to conceal information from parents also seems to be significantly related to further substance use and delinquency (Frijns et al 2005;Jaggi et al 2016). Adolescents who have low self-control may conceal more from their parents, but (based on the "muscle" or "strength" model of self-control) concealing information from parents may also reduce the capacity for self-control (Frijns et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As Darling and Tilton-Weaver (2019, p. 1) argue "revealing and concealing strategies are conceptually distinct from one another: an adolescent can reveal a great deal of information to parents about school activities while concealing their drinking". Previous research also suggests that the relationship between information management and adolescent outcomes is primarily the result of concealing strategies (Frijns et al 2010;Jaggi et al 2016). In other words, concealing strategies have a strong negative effect on adolescent outcomes, whereas disclosing strategies have a weak positive effect on adolescent outcomes.…”
Section: Adolescent Information Managementmentioning
confidence: 98%
See 1 more Smart Citation
“…La libre divulgation et les secrets gardés devraient donc être étudiés comme deux phénomènes à part entière (Frijns et al, 2010), ce que plusieurs travaux ont récemment confirmé (p. ex., Almas, Grusec, & Tackett, 2011 ;Jäggi, Drazdowski, & Kliewer, 2016 ;Lionetti, Keijsers, Dellagiulia, & Pastore, 2016).…”
Section: Les Secrets Gardésunclassified